(untitled) (Global Journal of Science Frontier Research, 2022)
Kumar provided the local convergence of a third convergent order method for solving equations defined on the real line. We study the semi-local convergence of this method defined on the real line or complex plain. The local convergence is also provided but under weaker conditions.